Perbedaan Hasil Belajar Ditinjau dari Gaya Belajar pada Mahasiswa di Fakultas Y, Universitas X, Jakarta - Widya Risnawaty; Maria Maria (Provitae: Jurnal Psikologi Pendidikan, 2014)
One of indicators to measure successedfrom the learning processis the resultof learning. There are some ways to measurestudent learning outcomes, one of whichis totest the knowledge of students about the material they had learned. In this study, the outcome variableis limited to the knowledge that students have learned about general psychology, scientific writing and philosophy. The literature suggests that there are several factors that may affect the learning outcomes, such as learning styles and curriculum. Learning style is the tendency of a person to use their skills related to sensory areas, when they process certain information. The four main abilities are according to Fleming (2012)is a visual, auditory, reading/writing, and kinesthetic. This study use quantitative method to test the correlation. The study involved two groups of respondents, they are: (a) 172 student from year 2011; and(b) 134 students from year 2012. The results show that there is no significant difference on learning outcomes in terms of learning styles from partisipant.Keywords: learning styles, learning outcomes, student